Internet of things: a research-oriented introductory. (2018) - Raja, S.P.; Sampradeepraj, T.
The world has shrunk considerably with the dramatic growth in internet usage. Every computer and mobile phone in the world can be connected together through internet technology. As a result, intelligent devices are connected and communicate together. The internet of things (IoT) envisions a future where people and intelligent systems cooperate and work together. In the IoT, machine-to-machine communication (M2M) helps devices exchange data, requiring power, efficiency, security and reliability. This paper advances new ideas for designing a security protocol in the IoT so as to facilitate secure M2M.